Trisodium phosphate and sodium hypochlorite are more effective as antimicrobials against Campylobacter and Salmonella on duck as compared to chicken meat - Sarjit, A.; Dykes, Gary (2015)
Little work has been reported on the use of commercial antimicrobials against foodborne pathogens on duck meat. We investigated the effectiveness of trisodium phosphate (TSP) and sodium hypochlorite (SH) as antimicrobial treatments against Campylobacter and Salmonella on duck meat under simulated commercial water chilling conditions. The results were compared to the same treatments on well-studied chicken meat. A six strain Campylobacter or Salmonella cocktail was inoculated (5 ml) at two dilution levels (104 and 108 cfu/ml) onto 25 g duck or chicken meat with skin and allowed to attach for 10 min. The meat was exposed to three concentrations of pH adjusted TSP (8, 10 and 12% (w/v), pH 11.5) or SH (40, 50 and 60 ppm, pH 5.5) in 30 ml water under simulated spin chiller conditions (4 °C, agitation) for 10 min. In a parallel experiment the meat was placed in the antimicrobial treatments before inoculation and bacterial cocktails were added to the meat after the antimicrobial solution was removed while all other parameters were maintained. Untreated controls and controls using water were included in all experiments. Bacterial numbers were determined on Campylobacter blood-free selective agar and Mueller Hinton agar or xylose deoxycholate agar and tryptone soya agar using the thin agar layer method for Campylobacter and Salmonella, respectively.All TSP concentrations significantly (p < 0.05) reduced numbers of Campylobacter (~ 1.2–6.4 log cfu/cm2) and Salmonella (~ 0.4–6.6 log cfu/cm2) on both duck and chicken meat. On duck meat, numbers of Campylobacter were less than the limit of detection at higher concentrations of TSP and numbers of Salmonella were less than the limit of detection at all concentrations of TSP except one. On chicken meat, numbers of Campylobacter and Salmonella were less than the limit of detection only at the lower inoculum level and higher TSP concentrations. By contrast only some of the concentrations of SH significantly (p < 0.05) reduced numbers of Campylobacter and Salmonella (~ 0.2–1.5 log cfu/cm2) on both duck and chicken meats. None of the SH treatments resulted in numbers of either pathogen being less than limit of detection. Results indicate that chicken meat has the ability to effectively protect Campylobacter and Salmonella against the impact of trisodium phosphate and sodium hypochlorite while duck meat does not. This study suggests that trisodium phosphate has a strong potential for application in a commercial poultry processing to reduce Campylobacter and Salmonella specifically on duck meat.